Chinook and Coho salmon hybrids linked to habitat and climatic changes on Vancouver Island, British Columbia. Issue 23 (11th November 2021) - Araujo, H. Andres; Duguid, William D. P.; Withler, Ruth; Supernault, Janine; Schulze, Angela D.; Mckenzie, Jessica L.; Pellett, Kevin; Beacham, Terry D.; Jonsen, Kim; Gummer, Anna
Abstract: Between 2013 and 2019, 63 presumed Chinook salmon Oncorhynchus tshawytscha sampled primarily in the Strait of Georgia (0.63% of total sample) were identified as potential Chinook–Coho ( Oncorhynchus kisutch ) hybrids by the presence of anomalous microsatellite genotypes. Their hybrid origin was confirmed by single nucleotide polymorphism amplification of two species‐specific amplicons. Mitochondrial DNA indicated that most of these fish resulted from the hybridization of Coho salmon females and Chinook salmon males. Although no diagnostic external features were identified, several individuals displayed an abnormal scale arrangement on the caudal peduncle. One hybrid juvenile examined for meristics exhibited a pyloric caeca count intermediate between published values for Chinook and Coho salmon. Most hybrids originated in the Cowichan River during the 2014 brood year. Their prevalence in the watershed is a naturally occurring event, likely exacerbated by prolonged low water levels which limit habitat and delay Chinook salmon spawning, in addition to the differential abundance of the parental species. This research is the first to document ongoing natural hybridization (Chinook–Coho salmon crosses) and link it to habitat and climatic changes, and includes the identification of eight F1 adults and two juvenile backcross or F2 hybrids. The potential negative impacts of hybridization, particularly in Coho salmon through potential introgression, warrant hybrid identification as an ecosystem monitoring tool within a survey program. Abstract : From 2013 to 2019, 63 presumed Chinook salmon sampled primarily in the Strait of Georgia were identified as potential Chinook–Coho hybrids. Their origin was confirmed by nuclear and mitochondrial DNA techniques. Changes in the hydrological regime and spawning time suggest that the observed hybridization is a process resulting from freshwater habitat modification and climatic pressures.